Inheritance: The Amount of Inheritance in Islam: The Struggle between Sharia Provisions, Social Dynamics, and Contemporary Scholars' Views in Normative and Perspectives - Amani, Rubi; Aliffah, Nurul; Rantika, Febriana Dwi; Ayu, Bening Frasiska; Putri, Bella Septi Yoana; Ramadhani, Aynayya; Aulia, Rayle Anggi; Al Ghifari, Muhammad Esa (Peneliti.net, 2025)
Inheritance law in classical Islam, as outlined in the Quran (Surah An-Nisa verse 11), establishes a fixed distribution pattern, for example, sons receiving twice the share of daughters. However, in current practice, there are social dynamics and demands for gender justice that challenge this pattern. This article explores the conflict between normative sharia law and sociological reality in inheritance arrangements, as well as how contemporary scholars (such as M. Syahrur) respond to this issue of gender inequality. The research employs a literature review (normative method) combined with sociological analysis and case studies. Findings indicate that although Islamic inheritance law is qath'i (definitive) by affirming inheritance portions based on sacred texts, social awareness and demands for equality drive reinterpretations or alternative legal solutions (such as a will) to reduce imbalance. Diagrams and tables are provided to illustrate inheritance distribution and compare opinions. Case studies related to inheritance calculations also highlight social justice issues. This paper emphasizes the relevance of gender inequality issues in the context of contemporary Muslim inheritance, highlighting the importance of synthesizing normative and sociological perspectives to achieve more equitable inheritance legal solutions. The uniqueness of this article lies in its comprehensive approach that combines sharia, social analysis, and contemporary views related to inheritance issues